Green bottle flies (Calliphoridae, Luciliinae) of Ecuador: geographic distribution, checklist and DNA barcodes - Moreno, Emilia (2020)
Green bottle flies (Diptera, Calliphoridae, Luciliinae) comprise a diverse and cosmopolitan taxon, known from at least 1,500 species. They have become crucial elements in forensic investigations, as they spend part of their life cycle in decaying remains. Here, we review the distribution of eleven Luciliinae species in Ecuador: the monotypic Blepharicnema and ten Lucilia species. We identified specimens using morphological characters. Additionally, we DNA barcoded 43 specimens from three species using 658bp segments of the standard Cytochrome Oxidase I (COI) mitochondrial gen. Molecular and morphological identifications presented high correspondence, suggesting COI barcodes are an efficient tool for the identification of these three green bottle flies species. Geographical records are biased towards the northern Andean region, particularly near to large urban settlements. We remark the value to applied forensic research of continuous sampling of necrophagous flies under a variety of habitats and crime conditions. © 2020 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.